Perceptions of the barriers, facilitators, outcomes, and helpfulness of strategies to implement screening, brief intervention, and referral to treatment in acute care - Alyson Keen; Kelli Thoele; Ukamaka Oruche; Robin Newhouse (Implementation Science, 2021)
Abstract Background Screening, Brief Intervention, and Referral to Treatment (SBIRT) is a clinical intervention used to address alcohol and illicit drug use. SBIRT use has resulted in positive health and social outcomes; however, SBIRT implementation remains low. Research on implementing interventions, such as SBIRT, lacks information about challenges and successes related to implementation. The Expert Recommendations for Implementing Change (ERIC) provides a framework to guide comprehension, clarity, and relevance of strategies available for implementation research. This framework was applied to qualitative feedback gathered from site coordinators (SCs) leading SBIRT implementation. The purpose of this study was to describe the SCs’ experiences pertaining to SBIRT implementation across a health system. Methods Within the context of a larger parent study, a semi-structured interview guide was used to capture 14 SCs’ perceptions of the barriers, facilitators, and outcomes pertaining to SBIRT implementation. Qualitative data were analyzed using standard content analytic procedures. A follow-up survey was developed based on 14 strategies identified from qualitative data and was administered electronically to determine the SC’s perceptions of the most helpful implementation strategies on a scale of 1 (least helpful) to 5 (most helpful). Results All 14 invited SCs participated in the SBIRT implementation interview, and 11 of 14 (79%) responded to the follow-up survey. Within the categories of barriers, facilitators, and outcomes, 25 subthemes emerged. The most helpful implementation strategies were reexamining the implementation (M = 4.38; n = 8), providing ongoing consultation (M = 4.13; n = 8), auditing and providing feedback (M = 4.1; n = 10), developing education materials (M = 4.1; n = 10), identifying and preparing champions (M = 4; n = 7), and tailoring strategies (M = 4; n = 7). Conclusion SCs who led implementation efforts within a large healthcare system identified several barriers and facilitators to the implementation of SBIRT. Additionally, they identified clinician-related outcomes associated with SBIRT implementation into practice as well as strategies that were helpful in the implementation process. This information can inform the implementation of SBIRT and other interventions in acute care settings.